Weather Information for Tribune - D. Bond; J. Slattery (Kansas Agricultural Experiment Station Research Reports, 2019)
Summary of 2018 weather for research conducted at the Tribune field location.
Keywords: Tribune weather; 2018 weather; southwest Kansas weather report